Effects of Vitamin C and E Supplementation on Growth, Fatty Acid Composition, Innate Immunity, and Antioxidant Capacity of Rainbow Trout (Oncorhynchus mykiss) Fed Oxidized Fish Oil - Rahimnejad, Samad; Dabrowski, Konrad; Izquierdo, Marisol; Hematyar, Nima; Imentai, Aiman; Steinbach, Christoph; Policar, Tomas (Frontiers in Marine Science, 2021)
This 10-week feeding experiment examined the effects of supplementing vitamin C (VC) and E (VE) in oxidized oil diets on growth, fatty acid composition, blood physiological indicators, innate immunity, antioxidant capacity, and liver and intestine histology of rainbow trout (Oncorhynchus mykiss). Four diets were produced including a fresh fish oil containing diet (FFO diet), an oxidized fish oil containing diet (OFO diet), and OFO diet supplemented with 500 mg kg-1 VC and 400 mg kg-1 VE (OFO+C500+E400 diet) or 1000 mg kg-1 VC and 800 mg kg-1 VE (OFO+C1000+E800 diet). Four hundred and twenty fish averaging 46.9 ± 0.32 g were stocked into 12 tanks and fed the diets twice a day to visual satiety. The results showed no significant effect of OFO or vitamins supplementation on growth, feed intake and feed utilization (P ˃ 0.05). The groups that received OFO and OFO+C1000+E800 diets had significantly (P ˂ 0.05) lower hepatosomatic indices than the other groups. Muscle fatty acid composition showed decreased proportion of 15:0, 16:0, 16:1n-7, 16:2n-4, 18:1n-5, 18:2n-6 (linoleic acid) and total saturated fatty acids in OFO group. Whereas higher percentages of 20:3n-6 and 20:3n-3 were found in OFO group. In addition, the highest ratio of docosahexaenoic acid (DHA, 22:6n-3) to eicosapentaenoic acid (EPA, 20:5n-3) was detected in OFO+C500+E400 group. The highest serum triglyceride concentration was recorded in the OFO group. Serum aspartate aminotransferase activity increased in OFO and OFO+C1000+E800 groups compared to OFO+C500+E400 group. Furthermore, significantly higher alkaline phosphatase activity in blood was found in OFO and OFO+C500+E400 groups. Significantly lower serum lysozyme, antiprotease, superoxide dismutase and catalase activities were recorded in OFO group compared to FFO and OFO+C500+E400 groups, and an opposite trend was observed for malondialdehyde concentration. Muscle VC and VE concentrations, and liver and intestine histology remained unaffected. To conclude, feeding diet containing oxidized oil with peroxide value of 182 meq kg-1 with/without VC and VE supplementation did not influence growth and tissue VC and VE concentrations of rainbow trout. However, supplementing 500 mg kg-1 VC and 400 mg kg-1 VE reversed the adverse effects of OFO on non-specific immune response and antioxidant capacity.